2010
DOI: 10.1636/p09-68.1
|View full text |Cite
|
Sign up to set email alerts
|

Additive partitioning of spider diversity in a fragmented tropical dry forest (Valle del Cauca, Colombia)

Abstract: Understanding the variation of diversity patterns requires analysis at multiple spatial scales. In this study we estimated the diversity components (alpha, beta and gamma) of the spider community at El Vínculo Natural Regional Park, using the additive partitioning of diversity (species richness, Shannon's diversity index and Simpson's index) for the first time on this taxon in Colombia. We collected the specimens following a nested sampling design that consisted of two spatial scales. At the local scale, we qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 29 publications
2
8
0
2
Order By: Relevance
“…This could be a reason for the lower cross-taxon correlations in b diversity, which is contrary to results in recent publications (Su et al 2004;Kessler et al 2009). A pattern that seems to be consistent across all taxa is that b diversity contributes in a large proportion to gamma diversity (Bermúdez-Rivas unpublished data), a pattern that have been found for spiders and predatory ants (ArcilaCardona et al 2008;Cabra-García et al 2010). Our results suggest that distance between sampling patches (Table 4) explain a very low percentage (0.006-6.760%) of the variation of b diversity across the sampling patches.…”
Section: Discussion a Diversitysupporting
confidence: 84%
“…This could be a reason for the lower cross-taxon correlations in b diversity, which is contrary to results in recent publications (Su et al 2004;Kessler et al 2009). A pattern that seems to be consistent across all taxa is that b diversity contributes in a large proportion to gamma diversity (Bermúdez-Rivas unpublished data), a pattern that have been found for spiders and predatory ants (ArcilaCardona et al 2008;Cabra-García et al 2010). Our results suggest that distance between sampling patches (Table 4) explain a very low percentage (0.006-6.760%) of the variation of b diversity across the sampling patches.…”
Section: Discussion a Diversitysupporting
confidence: 84%
“…4 Total abundance of adult and juvenile hunting spiders between the different types of habitat structure in southern Brazil (L low, I intermadiate, H high). Each box shows the median and the upper and lower quartiles, dashed lines represents the minimum and the maximum, and circles represents data points with abundance values Amaral 2001;Cabra-Garcı´a et al 2010;Cunha et al 2012;Rodrigues et al 2014). Immature spider individuals can represent adult spider community structure, generating similar results in community analyses when immature specimens are included or excluded (Sackett et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…complexity of vegetation) is the most relevant mechanism to explain the community structure (Soininen et al 2007;Losos et al 2010;Silva et al 2010). Habitats with low heterogeneity have low diversity of spiders (Greenstone 1984;Cabra-Garcı´a et al 2010). Cunha et al (2012) showed that the structure of habitats plays an important role to explain the differences in spider community composition.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent studies have shown that diversity patterns across spatial scales are not only taxon specific (i.e. mobile vs. sessile organism), but also dependent on the diversity measured (Ribeiro et al 2008;Garcia et al 2010;Flohre et al 2011). For dung beetles a high interspecific competition for dung resources could be expected (Hanski & Cambefort 1991), which may reduce diversity at the scale of the dung patch.…”
Section: Species Richness Across Land-use Types and Sampling Yearsmentioning
confidence: 99%
“…For example, Wagner et al (2000) used additive partitioning and concluded that β diversity among land-use types is more critical than β diversity between patches of the same land-use type in generating plant species richness in agricultural landscapes. Additive partitioning has been applied to several taxa, such as vegetation associations (Wagner et al 2000), birds (Fleishman et al 2003), beetles (Gering et al 2003), moths (Summerville & Crist 2005), and aquatic macroinvertebrate assemblages (Stendera & Johnson 2005), and spiders (Garcia et al 2010). However, the contribution of α and β diversity to regional diversity across a range of spatial scales remain unclear (Loreau 2000;.…”
Section: Introductionmentioning
confidence: 99%